Effect of Magnetic Graphene Oxide on Heavy Oil Demulsification - Dollah, Aqilah; Abu Bakar, Nurfarahain; Othman, Nur Hidayati; Che Mohamed Hussein, Siti Nurliyana; Japperi, Nur Shuhadah (International Journal of Integrated Engineering, 2022)
Chemical demulsification is the most efficient demulsification approach that can attain the desired separation efficiency and meet the environmental regulation standards whilst impose minimal economic burden on the petroleum industry. However, current demulsification methods using chemical demulsifiers suffer from significant secondary pollution, particularly after the demulsification process. Therefore, in this work, magnetic graphene oxide (MGO) was synthesized by a one-step co-precipitation method from graphene oxide (GO). The properties of MGO were then characterized by X-ray diffraction and Fourier transform infrared. MGO was successfully synthesized and used as the demulsifier for diluted heavy oil emulsions. Different MGO concentrations (40, 80, 120, 160, and 200 ppm) were used at different water cuts (20:80, 30:70, 40:60, 50:50, and 60:40 v/v%). Demulsification tests using the bottle test method indicated that MGO could separate the emulsions up to 99.98% efficiency due to the high surface area-to-volume ratio of nanoparticles and magnetic features, which enhanced the adsorptive capacity for separating water from the oil. The residual oil content in the separated water was then analyzed by an ultraviolet-visible spectrophotometer. The oil concentration in the separated water reduced to 398.8 mg/ml, corresponding to a demulsification efficiency of 99.98% observed at 40 ppm MGO concentration. The interfacial tension of the emulsions during demulsification was also analyzed, where the interfacial tension decreased with increasing MGO concentration.